Preparation method and application of deep coal and rock gas methane adsorbent based on graphene and MOF composite material

CN119869482AActive Publication Date: 2025-04-25SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202510227330.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-04-25
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

The existing deep coal rock gas methane adsorbents have shortcomings in terms of performance, cost and environmental friendliness, and are difficult to meet industrial needs, especially in the methane desorption process, which has problems of low efficiency and high energy consumption.

Method used

By synthesizing composite materials, the high specific surface area, conductivity and structural stability of graphene are complementary to the advantages of the rich active sites of MOF and the precise and adjustable pore structure of methane, thereby improving the adsorption and desorption efficiency of methane.

Benefits of technology

It achieves faster desorption rate, higher desorption efficiency and more stable desorption performance, significantly improves the adsorption capacity and selectivity of methane, and solves the problems of low efficiency and high energy consumption in the desorption process of traditional adsorbents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869482A_ABST
    Figure CN119869482A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a deep coal and rock gas methane adsorbent based on a graphene and MOF composite material, and belongs to the technical field of deep coal and rock gas methane adsorption and purification. The preparation method comprises the following steps: preparing a pretreated graphene material; mixing cadmium nitrate, 3-amino-4-picolinic acid and a solvent B until the mixture is completely dissolved to prepare a mixture; the mixture is subjected to a coordination reaction at a set temperature, then cooling crystallization is performed, crystals are washed and then dried, and Cd-MOF is prepared; adding the pretreated graphene material and Cd-MOF into a solvent A, then adding an auxiliary agent and a cross-linking agent, and carrying out a stirring reaction to prepare a composite material; adding a binder into the composite material, tabletting to obtain a molded composite material, and performing high-temperature activation treatment on the molded composite material in a protective atmosphere to obtain the deep coal rock gas methane adsorbent. The graphene and the MOF are synthesized into the composite material, and complementary advantages of the graphene and the MOF are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of deep coal-rock gas methane adsorption and purification, and specifically relates to a preparation method and application of a deep coal-rock gas methane adsorbent based on a graphene and MOF composite material. Background Art

[0002] Deep coal-rock gas is an important energy gas produced during the pyrolysis and gasification of coal. Its main component, methane, is an efficient and clean energy source with high economic value. However, the separation and recovery of methane in deep coal-rock gas has always been a key issue restricting its efficient utilization. Traditional methane adsorbents have many shortcomings in terms of performance, cost and environmental friendliness, making it difficult to meet the growing industrial needs.

[0003] At present, the commonly used method for separating methane from deep coal-rock gas is adsorption. Traditional adsorbents such as activated carbon and molecular sieves have some limitations in the adsorption and separation of methane from deep coal-rock gas. The pore size distribution of activated carbon is wide and difficult to precisely control, resulting in limited adsorption selectivity for methane. In a complex gas environment, it is difficult to efficiently separate and enrich methane; zeolite molecular sieves have regular pore structures and uniform pore sizes, and can screen different gases according to molecular size. They have a certain adsorption selectivity for methane, but their chemical activity is relatively low, and they are insufficient in promoting the desorption kinetics of methane, and the desorption process consumes a lot of energy.

[0004] Metal organic frameworks (MOFs) have precisely controllable pore structures, and have the advantages of high specific surface area, rich chemical functionality, and a large number of active sites, but MOF materials have disadvantages such as low mechanical strength, poor stability, and generally poor electrical conductivity. Graphene materials have high specific surface area and strong adsorption properties as well as good chemical stability and electrical conductivity, but they are easy to agglomerate, which reduces their specific surface area and effective active sites, affecting the adsorption of methane. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a preparation method and application of a deep coal gas methane adsorbent based on a graphene and MOF composite material, by synthesizing graphene and MOF into a composite material to achieve complementary advantages of the two. The high specific surface area, good conductivity and structural stability of graphene materials can make up for the problems of insufficient conductivity and poor stability of MOF materials; and the rich active sites and precisely controllable pore structure of MOF materials can solve the defects of single adsorption sites and limited adsorption selectivity of nanocarbon materials. This composite material has the excellent characteristics of both. In the process of methane desorption, it can achieve faster desorption rate, higher desorption efficiency and more stable desorption performance through synergistic effect.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a method for preparing a deep coal-rock gas methane adsorbent based on a graphene and MOF composite material, comprising the following steps: Dispersing graphene in solvent A to obtain a dispersion; then adding an acidifying agent to the dispersion, heating and stirring to perform an acidification reaction, and then centrifuging, washing and drying in sequence to obtain a pretreated graphene material; Cadmium nitrate, 3-amino-4-pyridinecarboxylic acid and solvent B are mixed until they are completely dissolved to obtain a mixture; the mixture is placed at a set temperature to undergo a coordination reaction, then cooled and crystallized, the crystals are washed and dried to obtain Cd-MOF; The pretreated graphene material and Cd-MOF are added to solvent A, and then an auxiliary agent and a cross-linking agent are added and stirred to react to obtain a composite material; a binder is added to the composite material, and then the composite material is pressed into a sheet to obtain a molded composite material, and then the molded composite material is subjected to high-temperature activation treatment under a protective atmosphere to obtain a deep coal gas methane adsorbent.

[0007] In one implementation process, the mass volume ratio of graphene and solvent A in the dispersion is (0.01-0.03 g):1 mL; the volume ratio of the dispersion and the acidifying agent is (4-5):1.

[0008] In one implementation process, the solvent A is a mixed solution of N,N-dimethylformamide, ethanol and acetonitrile; wherein the volume ratio of N,N-dimethylformamide, ethanol and acetonitrile is 6:3:1.

[0009] In one implementation process, the acidifying agent is a mixture of concentrated sulfuric acid and hydrogen peroxide, and the volume ratio of the concentrated sulfuric acid to hydrogen peroxide is (5-7):1; The heating and stirring time is 3-4h; the temperature of the acidification reaction is 70-80°C.

[0010] In one implementation process, the molar ratio of cadmium nitrate to 3-amino-4-pyridinecarboxylic acid is 1:(1-3); the ratio of cadmium nitrate to solvent B is 0.001 mol corresponding to 20-30 mL; The solvent B consists of N,N-dimethylformamide, acetonitrile and water, and the volume ratio of N,N-dimethylformamide, acetonitrile and water is 6:3:1.

[0011] In one implementation process, the set temperature is 100° C., the coordination reaction time is 22-24 hours, and the cooling rate of the cooling crystallization is 13-15° C. / h.

[0012] In one implementation, the mass ratio of the pretreated graphene material to Cd-MOF is 1:(0.5-1); The ratio of the total mass of the pretreated graphene material and Cd-MOF to the volume of solvent A is (0.01-0.05) g:1 mL.

[0013] In one implementation, the auxiliary agent is sodium dodecylbenzene sulfonate, the cross-linking agent is glutaraldehyde, and the binder is polyvinyl alcohol or sodium carboxymethyl cellulose; The amount of the auxiliary agent is 1%-3% of the total mass of the pretreated graphene material and Cd-MOF; The amount of the cross-linking agent is 5%-10% of the total mass of the pretreated graphene material and Cd-MOF; The amount of the binder used is 1%-3% of the mass of the composite material.

[0014] In one implementation process, the stirring reaction temperature is 40-50° C., and the stirring reaction time is 10-12 h; The protective atmosphere is nitrogen, the temperature of the high-temperature activation treatment is 300-400° C., and the time of the high-temperature activation treatment is 3-4 hours.

[0015] The present invention also provides an application of a deep coal-rock gas methane adsorbent based on a graphene and MOF composite material prepared by the preparation method of the deep coal-rock gas methane adsorbent based on a graphene and MOF composite material as described above in a methane adsorption process.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a deep coal-rock gas methane adsorbent based on a graphene and MOF composite material. A new composite material is prepared by compounding graphene with MOF, giving full play to the advantages of the two and achieving complementarity. Since graphene materials have a high specific surface area, excellent electrical conductivity and good structural stability, they can effectively improve the poor electrical conductivity and insufficient stability of MOF materials. The rich active sites and precisely controllable pore structure of MOF materials can just make up for the defects of single adsorption sites and limited adsorption selectivity of graphene materials. In the process of methane desorption, the two produce a significant synergistic effect, so that the composite material exhibits a faster desorption rate and can complete the desorption operation in a shorter time; it has a higher desorption efficiency and can achieve efficient desorption of methane; at the same time, it has a more stable desorption performance, and can still maintain good performance in multiple cycles of desorption, providing a better material selection for methane-related applications. The methane adsorbent prepared by the present invention has the advantages of good methane adsorption selectivity, large specific surface area, high methane adsorption rate, good adsorption separation effect, adjustable pore size, high adsorption efficiency, etc., can realize efficient desorption and utilization of methane, and solve the problems existing in the desorption process of existing methane adsorbents.

[0017] Furthermore, pretreatment of graphene can enhance its compatibility with other substances, making the graphene sheets evenly dispersed in the solvent and forming a better interface with the MOF material. At the same time, the impurities in the graphene are removed by acidification treatment to improve the consistency and repeatability of the performance of the graphene material. The pretreated graphene is compounded with Cd-MOF to prepare a methane adsorbent. Compared with other traditional adsorbents, graphene has a huge specific surface area, and Cd-MOF has a rich and regular pore structure. The combination of the two can produce a synergistic effect and provide more adsorption sites, thereby significantly improving the adsorption capacity for methane and greatly improving the methane adsorption rate.

[0018] Furthermore, compared with other products, the pore size and chemical environment of Cd-MOF of the product of the present invention can be precisely controlled, so that it has a specific affinity and selectivity for methane molecules. After the graphene is compounded with Cd-MOF, the surface properties and pore structure of the adsorbent are further optimized, and the methane molecules can be more effectively identified and adsorbed, the interference of other gases is reduced, and the adsorption selectivity of methane is improved. The two-dimensional structure of graphene is conducive to molecular diffusion. After compounding with Cd-MOF, the diffusion rate of methane molecules inside the adsorbent can be accelerated, so that the adsorption process quickly reaches equilibrium and exhibits faster adsorption kinetics. At the same time, the interface area formed between graphene and Cd-MOF can provide additional diffusion channels and paths for guest molecules, so that the adsorbed molecules can diffuse more quickly from the inside of the composite material to the external environment during the desorption process, thereby improving the desorption efficiency.

[0019] Furthermore, Cd-MOF itself has a certain chemical stability, and the introduction of graphene can enhance the chemical stability of the composite material. The carbon atoms of graphene are tightly bound by covalent bonds to form a stable two-dimensional structure, which can resist the erosion of some chemical substances, protect Cd-MOF from the influence of the external environment, and enable the adsorbent to maintain stable adsorption performance in different chemical environments. Due to its special structure and surface properties, under low temperature or pressure change conditions, methane molecules can be desorbed from the adsorbent surface, realizing the recycling and reuse of the adsorbent. After multiple adsorption-desorption cycles, the structure and adsorption performance of the graphene and Cd-MOF composite material can remain relatively stable, and still maintain a high adsorption capacity and selectivity.

[0020] In summary, the preparation method of the composite material methane adsorbent of the present invention has a simple process, low raw material cost, and is easy to control. The obtained activated carbon for methane adsorption has a high specific surface area, high adsorption efficiency and rate, good stability, and is easy to recycle and reuse. It can efficiently adsorb methane gas through the synergistic adsorption of physical and chemical adsorption, produce excellent adsorption effects, have a long service life, and have low methane purification costs. It effectively solves the technical problem of poor methane adsorption effect of activated carbon in the prior art and has extremely strong practicality. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the adsorption isotherm diagram of the deep coal gas methane adsorbent based on graphene and MOF composite material prepared in Example 3 of the present invention at 273K. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0023] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0024] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0025] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0026] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0027] The present invention provides a method for preparing a deep coal-rock gas methane adsorbent based on a graphene and MOF composite material, the preparation method comprising: The graphene is dispersed in a first organic solvent (solvent A), and ultrasonically treated to fully disperse the graphene to obtain a dispersion; an acidifying agent is added to the dispersion, and the dispersion is heated and stirred to perform an acidification reaction. After the reaction is completed, the dispersion is centrifuged, washed, and dried to obtain a pretreated graphene material; Cadmium nitrate, 3-amino-4-pyridinecarboxylic acid, and solvent B consisting of N,N-dimethylformamide, acetonitrile, and water were mixed and added to a sealed glass bottle and fully shaken in an ultrasonic cleaner until completely dissolved. The dissolved mixture was placed in an oven at 100° C. for reaction, cooled and crystallized, the crystals were washed, and dried to obtain Cd-MOF; The pretreated graphene material and Cd-MOF are added to the second organic solvent (another solvent A) and ultrasonically treated. Then, an auxiliary agent and a cross-linking agent are added, stirred and reacted to obtain a composite material; a binder is added to the composite material, and the composite material is pressed into a desired shape and size. The formed composite material is activated under nitrogen protection to obtain the final product.

[0028] The composite material for methane adsorbent obtained by the present invention has the advantages of good methane adsorption selectivity, large specific surface area, high methane adsorption rate, good adsorption separation effect, adjustable pore size, high adsorption efficiency, etc., and has good stability, easy recycling and reuse, and good desorption efficiency. The hybrid material of the present invention produces efficient adsorption of methane gas through physical and chemical synergistic adsorption, effectively solves the technical problem of poor methane adsorption effect of activated carbon in the prior art, and has strong practicality.

[0029] The first aspect of the present invention provides a method for preparing a deep coal gas methane adsorbent, the preparation method is based on a graphene and MOF composite material, and the specific preparation method includes: (1) dispersing graphene in a first organic solvent (solvent A), subjecting the dispersion to ultrasonic treatment to fully disperse the graphene, and preparing a dispersion liquid; adding an acidifying agent to the dispersion liquid, heating and stirring the dispersion liquid to perform an acidification reaction, and after the acidification reaction is completed, centrifuging and washing the dispersion liquid, and drying the dispersion liquid to obtain a pretreated graphene material; (2) Mix cadmium nitrate, 3-amino-4-pyridinecarboxylic acid, N,N-dimethylformamide, acetonitrile and water into a sealed glass bottle and shake thoroughly in an ultrasonic cleaner until completely dissolved. Place the dissolved mixture in an oven at 100°C to undergo coordination reaction, cool and crystallize, wash the crystals, and dry to obtain Cd-MOF. (3) adding the pretreated graphene material and Cd-MOF to a second organic solvent (solvent A), performing ultrasonic treatment, then adding an auxiliary agent and a cross-linking agent, stirring and reacting, and obtaining a composite material; (4) Add a binder to the composite material and press it into a desired shape and size. Activate the formed composite material under nitrogen protection to obtain the final product.

[0030] The first organic solvent (solvent A) and the second organic solvent (another solvent A) are the same, and both the first organic solvent (solvent A) and the second organic solvent (another solvent A) are mixed solutions of N,N-dimethylformamide, ethanol and acetonitrile; wherein the mass ratio of N,N-dimethylformamide, ethanol and acetonitrile is 6:3:1.

[0031] In step (1), the mass volume ratio of graphene and the first organic solvent (solvent A) is (0.01-0.03 g):1 mL; the volume ratio of the dispersion liquid to the acidifying agent is (4-5):1; the acidifying agent is a mixed solution of concentrated sulfuric acid and hydrogen peroxide, and the volume ratio of the two is (5-7):1; the ultrasonic treatment time is 1-1.5 h; the reaction temperature is 70-80 ° C, and the stirring time is 3-4 h.

[0032] In step (2), the molar ratio of cadmium nitrate to 3-amino-4-pyridinecarboxylic acid is 1:(1-3), and the volume ratio of N,N-dimethylformamide, acetonitrile and water in the solvent is 6:3:1. Solvent B is composed of N,N-dimethylformamide, acetonitrile and water, and the ratio of cadmium nitrate to solvent B is 0.001 mol corresponding to 20-30 mL. The coordination reaction time is 22-24 hours; the cooling rate of cooling crystallization is 13-15°C / h.

[0033] In step (3), the mass ratio of the pretreated graphene to Cd-MOF is 1:(0.5-1), and the mass volume ratio of the two to the second organic solvent (another solvent A) is (0.01-0.05 g):1 mL. The second organic solvent (another solvent A) is a mixed solution of N,N-dimethylformamide, ethanol and acetonitrile, and the ratio of the three is 6:3:1; the ultrasonic treatment time in step (3) is 1-1.5 hours.

[0034] In step (3), the auxiliary agent is sodium dodecylbenzene sulfonate (SDBS), and the cross-linking agent is glutaraldehyde; the amount of the auxiliary agent is 1%-3% of the total mass of the pretreated graphene and Cd-MOF, and the amount of the cross-linking agent is 5%-10% of the total mass; the reaction temperature is 40-50°C, and the reaction time is 10-12 h.

[0035] The binder used in step (4) is polyvinyl alcohol or sodium carboxymethyl cellulose, and the amount of the binder is 1%-3% of the mass of the composite material; the activation reaction temperature is 300°C-400°C, and the reaction time is 3-4h.

[0036] As a further illustration of the present invention, to a certain extent, graphene will partially coat Cd-MOF particles. The SDBS molecules adsorbed on the graphene and Cd-MOF surfaces form an adsorption layer with a certain thickness. When the particles are close to each other, this adsorption layer will produce steric hindrance, preventing the particles from further aggregating, thereby maintaining their dispersed state. The two aldehyde groups of glutaraldehyde can react with nucleophilic groups such as amino groups and hydroxyl groups on the surfaces of graphene and Cd-MOF under suitable reaction conditions. Through the above chemical reaction, covalent bonds are formed between glutaraldehyde, graphene and Cd-MOF. SDBS improves the dispersibility of graphene, allowing it to better contact Cd-MOF, and under the cross-linking effect of glutaraldehyde, graphene can surround Cd-MOF to form a coating structure. This structure can protect the structural stability of Cd-MOF, while also increasing the specific surface area and adsorption sites of the composite material.

[0037] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0038] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0039] Example 1 (1) Disperse 10 g of graphene in 1000 mL of a first organic solvent mixed with N,N-dimethylformamide, ethanol, and acetonitrile, and perform ultrasonic treatment for 1.5 h to fully disperse the graphene to obtain a dispersion. Add 25 mL of a concentrated sulfuric acid-hydrogen peroxide mixture to the 100 mL dispersion, with the volume ratio of concentrated sulfuric acid to hydrogen peroxide being 5:1, and stir at 80°C for 4 h for acidification reaction. After the acidification reaction is completed, centrifuge and wash, and dry at 50°C for 4 h to obtain the pretreated graphene material. (2) 2.36 g of cadmium nitrate, 1.38 g of 3-amino-4-pyridinecarboxylic acid, 120 mL of N,N-dimethylformamide, 60 mL of acetonitrile and 20 mL of deionized water were mixed and added to a sealed glass bottle and fully shaken in an ultrasonic cleaner until completely dissolved. The dissolved mixture was placed in an oven at 100 °C for 24 h, cooled and crystallized at a cooling rate of 13 °C / h, the crystals were washed and dried to obtain Cd-MOF; (3) 4 g of pretreated graphene and 2 g of Cd-MOF were mixed and added to 600 mL of a second organic solvent mixed with N,N-dimethylformamide, ethanol, and acetonitrile, and ultrasonically treated for 1.5 h. Then, 0.18 g of dodecylbenzenesulfonic acid as an auxiliary agent and 0.6 g of glutaraldehyde as a cross-linking agent were added, and the mixture was stirred at 50 °C for 12 h to obtain a composite material; (4) Add 0.15 g of polyvinyl alcohol as a binder to 5 g of the composite material and press it into a desired shape and size. The formed composite material is activated at 400 °C for 4 h under nitrogen protection to obtain the final product.

[0040] Example 2 (1) Disperse 30 g of graphene in 1000 mL of a first organic solvent mixed with N,N-dimethylformamide, ethanol, and acetonitrile, and perform ultrasonic treatment for 1.5 h to fully disperse the graphene to obtain a dispersion. Add 20 mL of a concentrated sulfuric acid-hydrogen peroxide mixture to the 100 mL dispersion, with the volume ratio of concentrated sulfuric acid to hydrogen peroxide being 5:1, and stir at 80°C for 4 h for acidification reaction. After the acidification reaction is completed, centrifuge and wash, and dry at 50°C for 4 h to obtain the pretreated graphene material. (2) 2.36 g of cadmium nitrate, 2.76 g of 3-amino-4-pyridinecarboxylic acid, 120 mL of N,N-dimethylformamide, 60 mL of acetonitrile and 20 mL of deionized water were mixed and added to a sealed glass bottle and fully shaken in an ultrasonic cleaner until completely dissolved. The dissolved mixture was placed in an oven at 100 °C for 24 h, cooled and crystallized at a cooling rate of 13 °C / h, the crystals were washed and dried to obtain Cd-MOF; (3) 4 g of pretreated graphene and 4 g of Cd-MOF were mixed and added to 600 mL of a second organic solvent mixed with N,N-dimethylformamide, ethanol, and acetonitrile, and ultrasonically treated for 1 h. Then, 0.18 g of dodecylbenzenesulfonic acid as an auxiliary agent and 0.6 g of glutaraldehyde as a cross-linking agent were added, and the mixture was stirred at 50 °C for 12 h to obtain a composite material; (4) Add 0.15 g of polyvinyl alcohol as a binder to 5 g of the composite material and press it into a desired shape and size. The formed composite material is activated at 400 °C for 4 h under nitrogen protection to obtain the final product.

[0041] Example 3 (1) Disperse 10 g of graphene in 1000 mL of a first organic solvent mixed with N,N-dimethylformamide, ethanol, and acetonitrile, and perform ultrasonic treatment for 1 h to fully disperse the graphene to obtain a dispersion. Add 25 mL of a concentrated sulfuric acid-hydrogen peroxide mixture to the 100 mL dispersion, with the volume ratio of concentrated sulfuric acid to hydrogen peroxide being 5:1, and stir at 80°C for 3 h for acidification reaction. After the acidification reaction is completed, centrifuge and wash, and dry at 50°C for 4 h to obtain the pretreated graphene material. (2) 2.36 g of cadmium nitrate, 4.14 g of 3-amino-4-pyridinecarboxylic acid, 120 mL of N,N-dimethylformamide, 60 mL of acetonitrile and 20 mL of deionized water were mixed and added to a sealed glass bottle and fully shaken in an ultrasonic cleaner until completely dissolved. The dissolved mixture was placed in an oven at 100 °C for 24 h, cooled and crystallized at a cooling rate of 13 °C / h, the crystals were washed and dried to obtain Cd-MOF; (3) 4 g of pretreated graphene and 4 g of Cd-MOF were mixed and added to 480 mL of a second organic solvent mixed with N,N-dimethylformamide, ethanol, and acetonitrile, and ultrasonically treated for 1.5 h. Then, 0.18 g of dodecylbenzenesulfonic acid as an auxiliary agent and 0.6 g of glutaraldehyde as a cross-linking agent were added, and the mixture was stirred at 40 °C for 10 h to obtain a composite material; (4) Add 0.15 g of sodium carboxymethyl cellulose as a binder to 5 g of the composite material and press the composite material into a desired shape and size. The composite material after molding is activated at 300 °C for 4 h under nitrogen protection to obtain the final product.

[0042] Example 4 (1) Disperse 30 g of graphene in 1000 mL of a first organic solvent mixed with N,N-dimethylformamide, ethanol, and acetonitrile, and perform ultrasonic treatment for 1 h to fully disperse the graphene to obtain a dispersion. Add 25 mL of a concentrated sulfuric acid-hydrogen peroxide mixture to the 100 mL dispersion, with the volume ratio of concentrated sulfuric acid to hydrogen peroxide being 5:1, and stir at 70°C for 3 h to perform an acidification reaction. After the acidification reaction is completed, centrifuge and wash, and dry at 50°C for 4 h to obtain the pretreated graphene material. (2) 2.36 g of cadmium nitrate, 2.76 g of 3-amino-4-pyridinecarboxylic acid, 120 mL of N,N-dimethylformamide, 60 mL of acetonitrile and 20 mL of deionized water were mixed and added to a sealed glass bottle and fully shaken in an ultrasonic cleaner until completely dissolved. The dissolved mixture was placed in an oven at 100 °C for 22 h, cooled and crystallized at a cooling rate of 15 °C / h, the crystals were washed and dried to obtain Cd-MOF; (3) 4 g of pretreated graphene and 3 g of Cd-MOF were mixed and added to 360 mL of a second organic solvent mixed with N,N-dimethylformamide, ethanol, and acetonitrile, and ultrasonically treated for 1 h. Then, 0.18 g of dodecylbenzenesulfonic acid as an auxiliary agent and 0.3 g of glutaraldehyde as a cross-linking agent were added, and the mixture was stirred at 50 °C for 12 h to obtain a composite material; (4) Add 0.05 g of sodium carboxymethyl cellulose as a binder to 5 g of the composite material and press the composite material into a desired shape and size. The composite material after molding is activated at 300 °C for 4 h under nitrogen protection to obtain the final product.

[0043] Example 5 (1) Disperse 20 g of graphene in 1000 mL of a first organic solvent mixed with N,N-dimethylformamide, ethanol, and acetonitrile, and perform ultrasonic treatment for 1.5 h to fully disperse the graphene to obtain a dispersion. Add 20 mL of a concentrated sulfuric acid-hydrogen peroxide mixture to the 100 mL dispersion, with the volume ratio of concentrated sulfuric acid to hydrogen peroxide being 6:1, and stir at 70°C for 4 h for acidification reaction. After the acidification reaction is completed, centrifuge and wash, and dry at 50°C for 4 h to obtain the pretreated graphene material. (2) 2.36 g of cadmium nitrate, 2.76 g of 3-amino-4-pyridinecarboxylic acid, 120 mL of N,N-dimethylformamide, 60 mL of acetonitrile and 20 mL of deionized water were mixed and added to a sealed glass bottle and fully shaken in an ultrasonic cleaner until completely dissolved. The dissolved mixture was placed in an oven at 100 °C for 22 h, cooled and crystallized at a cooling rate of 15 °C / h, the crystals were washed and dried to obtain Cd-MOF; (3) 4 g of pretreated graphene and 2 g of Cd-MOF were mixed and added to 240 mL of a mixed organic solvent of N,N-dimethylformamide, ethanol, and acetonitrile, and ultrasonically treated for 1.5 h. Then, 0.15 g of dodecylbenzenesulfonic acid as an auxiliary agent and 0.3 g of glutaraldehyde as a cross-linking agent were added, and the mixture was stirred at 40 °C for 10 h to obtain a composite material; (4) Add 0.05 g of polyvinyl alcohol as a binder to 5 g of the composite material and press it into the desired shape and size. The formed composite material is activated at 400 °C for 3 h under nitrogen protection to obtain the final product.

[0044] Example 6 (1) Disperse 20 g of graphene in 1000 mL of a first organic solvent mixed with N,N-dimethylformamide, ethanol, and acetonitrile, and perform ultrasonic treatment for 1 h to fully disperse the graphene to obtain a dispersion. Add 20 mL of a concentrated sulfuric acid-hydrogen peroxide mixture to the 100 mL dispersion, with the volume ratio of concentrated sulfuric acid to hydrogen peroxide being 7:1, and stir at 70°C for 4 h for acidification reaction. After the acidification reaction is completed, centrifuge and wash, and dry at 50°C for 4 h to obtain the pretreated graphene material. (2) 2.36 g of cadmium nitrate, 1.38 g of 3-amino-4-pyridinecarboxylic acid, 120 mL of N,N-dimethylformamide, 60 mL of acetonitrile and 20 mL of deionized water were mixed and added to a sealed glass bottle and fully shaken in an ultrasonic cleaner until completely dissolved. The dissolved mixture was placed in an oven at 100 °C for 23 h, cooled and crystallized at a cooling rate of 14 °C / h, the crystals were washed and dried to obtain Cd-MOF; (3) 4 g of pretreated graphene and 2 g of Cd-MOF were mixed and added to 120 mL of a mixed organic solvent of N,N-dimethylformamide, ethanol, and acetonitrile, and ultrasonically treated for 1.5 h. Then, 0.12 g of dodecylbenzenesulfonic acid as an auxiliary agent and 0.6 g of glutaraldehyde as a cross-linking agent were added, and the mixture was stirred at 50 °C for 10 h to obtain a composite material; (4) Add 0.1 g of sodium carboxymethyl cellulose as a binder to 5 g of the composite material and press it into a desired shape and size. The formed composite material is activated at 400 °C for 3 h under nitrogen protection to obtain the final product.

[0045] In order to characterize the effect of different synthesis conditions on the dynamic adsorption capacity and specific surface area of ​​the methane adsorbent, the adsorbents synthesized in Examples 1-6 were tested for dynamic adsorption capacity, specific surface area, and micropore volume. The stability of the methane adsorbent was investigated through a cycle-desorption cycle experiment. The results are shown in Table 1.

[0046] Table 1 Performance tests of methane adsorbent

[0047] The research results show that the composite methane adsorbent exhibits extremely high adsorption capacity. Under standard temperature and pressure conditions, the methane adsorbent prepared by this product has a maximum dynamic adsorption capacity of 82.8 mL / g for methane, which is higher than the average level of similar adsorbents on the market. In a complex gas mixture environment, it shows excellent selectivity for methane. The adsorbent has excellent desorption performance. After multiple cycle-desorption experiments, the adsorption efficiency can still reach up to 90.1%, and the desorption efficiency can reach up to 94.6%. This enables the adsorbent to quickly and effectively release the adsorbed methane after completing the adsorption task, which is convenient for the recycling of methane and also provides good conditions for the recycling of the adsorbent. It has a huge specific surface area, up to 1823.8 m² / g, and there are a large number of regular micropores and mesopores inside, which provide abundant adsorption sites for the adsorption of methane. At the same time, the composite methane adsorbent is environmentally friendly during production and use, does not contain harmful substances, and does not pollute the environment. After being discarded, it is also easy to handle and can be recycled through simple regeneration or recycling processes, which meets the development requirements of modern green environmental protection.

[0048] like Figure 1 As shown in the figure, the methane adsorbent for deep coal gas prepared in Example 3 increases the adsorption of methane with the increase of absolute pressure under the environment of 273 K. In the lower pressure range, the adsorption amount increases rapidly with the increase of pressure, and as the pressure increases further in the later period, the growth rate of the adsorption amount gradually slows down. This is because the adsorption sites on the surface of the adsorbent are gradually occupied and reach a state close to saturation, and the effect of increasing the pressure on the adsorption amount is no longer significant.

[0049] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a deep coal gas methane adsorbent based on graphene and MOF composite materials, characterized in that: The following steps are involved: Dispersing graphene in solvent A to obtain a dispersion; then adding an acidifying agent to the dispersion, heating and stirring to perform an acidification reaction, and then centrifuging, washing and drying in sequence to obtain a pretreated graphene material; Cadmium nitrate, 3-amino-4-pyridinecarboxylic acid and solvent B are mixed until they are completely dissolved to obtain a mixture; the mixture is placed at a set temperature to undergo a coordination reaction, then cooled and crystallized, the crystals are washed and dried to obtain Cd-MOF; The pretreated graphene material and Cd-MOF are added to solvent A, and then an auxiliary agent and a cross-linking agent are added and stirred to react to obtain a composite material; a binder is added to the composite material, and then the composite material is pressed into a sheet to obtain a molded composite material, and then the molded composite material is subjected to high-temperature activation treatment under a protective atmosphere to obtain a deep coal gas methane adsorbent.

2. The method for preparing a deep coal gas methane adsorbent based on a graphene and MOF composite material according to claim 1, characterized in that: The mass volume ratio of graphene and solvent A in the dispersion is (0.01-0.03 g):1 mL; the volume ratio of the dispersion and the acidifying agent is (4-5):

1.

3. The method for preparing a deep coal gas methane adsorbent based on a graphene and MOF composite material according to claim 1, characterized in that: The solvent A is a mixed solution of N,N-dimethylformamide, ethanol and acetonitrile; wherein the volume ratio of N,N-dimethylformamide, ethanol and acetonitrile is 6:3:

1.

4. The method for preparing a deep coal gas methane adsorbent based on a graphene and MOF composite material according to claim 1, characterized in that: The acidifying agent is a mixture of concentrated sulfuric acid and hydrogen peroxide, and the volume ratio of the concentrated sulfuric acid to hydrogen peroxide is (5-7):1; The heating and stirring time is 3-4h; the temperature of the acidification reaction is 70-80°C.

5. The method for preparing a deep coal gas methane adsorbent based on a graphene and MOF composite material according to claim 1, characterized in that: The molar ratio of the cadmium nitrate to 3-amino-4-pyridinecarboxylic acid is 1:(1-3); the ratio of the cadmium nitrate to solvent B is 0.001 mol corresponding to 20-30 mL; The solvent B consists of N,N-dimethylformamide, acetonitrile and water, and the volume ratio of N,N-dimethylformamide, acetonitrile and water is 6:3:

1.

6. The method for preparing a deep coal gas methane adsorbent based on a graphene and MOF composite material according to claim 1, characterized in that: The set temperature is 100° C., the coordination reaction time is 22-24 hours, and the cooling rate of the cooling crystallization is 13-15° C. / h.

7. The method for preparing a deep coal gas methane adsorbent based on a graphene and MOF composite material according to claim 1, characterized in that: The mass ratio of the pretreated graphene material to Cd-MOF is 1:(0.5-1); The ratio of the total mass of the pretreated graphene material and Cd-MOF to the volume of solvent A is (0.01-0.05) g:1 mL.

8. The method for preparing a deep coal gas methane adsorbent based on a graphene and MOF composite material according to claim 1, characterized in that: The auxiliary agent is sodium dodecylbenzene sulfonate, the cross-linking agent is glutaraldehyde, and the binder is polyvinyl alcohol or sodium carboxymethyl cellulose; The amount of the auxiliary agent is 1%-3% of the total mass of the pretreated graphene material and Cd-MOF; The amount of the cross-linking agent is 5%-10% of the total mass of the pretreated graphene material and Cd-MOF; The amount of the binder used is 1%-3% of the mass of the composite material.

9. The method for preparing a deep coal gas methane adsorbent based on a graphene and MOF composite material according to claim 1, characterized in that: The stirring reaction temperature is 40-50°C, and the stirring reaction time is 10-12h; The protective atmosphere is nitrogen, the temperature of the high-temperature activation treatment is 300-400° C., and the time of the high-temperature activation treatment is 3-4 hours.

10. Use of the deep coal-rock gas methane adsorbent based on graphene and MOF composite materials obtained by the preparation method of the deep coal-rock gas methane adsorbent based on graphene and MOF composite materials as described in any one of claims 1 to 9 in the methane adsorption process.

Citation Information

Patent Citations

  • Metal-organic framework material for methane adsorption and storage and preparation method thereof

    CN103100372A

  • Bimetal organic framework material as well as preparation and application thereof

    CN106673992A

  • Preparation method of graphene / metal organic frame aerogel adsorbing / catalyzing material

    CN107376837A

  • Graphene oxide / metal organic frame composite film, preparation method and application thereof

    CN110270234A

  • Systems and methods for gas storage and transportation using MOFs with bis (pyrazolyl) ethanediimine ligands

    CN115175761A

Cited By

  • Preparation method of temperature-resistant nano alkenyl gas desorption agent and application of temperature-resistant nano alkenyl gas desorption agent in coal mine drainage and mining

    CN121775822A